Labor Mobility Across The Formal/Informal Divide in Turkey: Evidence From Individual Level Data - Aysit Tansel; Elif Oznur Kan (Turkish Economic Association, 2012)
Informality has long been a salient phenomenon in developing country labor markets, thus has been addressed in several theoretical and empirical research. Turkey, given its economic and demographic dynamics, provides rich evidence for a growing, heterogeneous and multifaceted informal labor market. However, the existing evidence on labor informality in Turkey is mixed and scant. Along these lines, we aim to extend the existing literature by providing a diagnosis of dynamic worker flows across distinct labor market states and identifying the effects of certain individual and job characteristics on variant mobility patterns. More specifically, we first develop and discuss a set of probability statistics based on annual worker transitions across distinct employment states utilizing Markov transition processes. As Bosch and Maloney (2007:3) argue: labor status mobility can be assumed as a process in which changes in the states occur randomly through time, and probabilities of moves between particular states are governed by Markov transition matrices. Towards this end, we will use the novel Income and Living Conditions Survey (SILC) panel data set to compute the transition probabilities of individuals moving across the labor market states of formal-salaried, informal-salaried, formal self-employed, informal self-employed, unemployed and inactive. The transitions analysis is conducted separately for two, three and four year panels pertaining to 2006 to 2007, 2006 to 2008 and 2006 to 2009 transitions; for total, male and female samples; and lastly for total and non-agricultural samples. In this way, we aim to contribute to the limited body of stylized facts available on mobility and informality in the Turkish labor market. Next, we conduct multinomial logit regressions individually for each set of panel to identify the impact of individual characteristics (i.e. gender, age, education level, work experience, sector of economic activity, firm size, number of other household members, having/not having children, rural/urban) underlying worker transitions. The results reveal several relationships between the covariates and likelihood of variant transitions, and are of remarkable importance for designing policy to adress labor informality and reduce its negative externalities.
Keywords: J21; J24; J40; J63; O17; 330; Labor market dynamics; informality; Markov processes; multinomial logit; Turkey; Arbeitsplatzwechsel; Informeller Sektor; Arbeitsmobilität; Stochastischer Prozess; Logit-Modell; Schätzung; Türkei